2002
DOI: 10.1002/1521-4079(200208)37:8<841::aid-crat841>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Host Lattice Effect on Paramagnetic Impurity: Single Crystal EPR Study of VO(II)-Doped Biomineral Cadmium Ammonium Phosphate Hexahydrate

Abstract: Single crystal electron paramagnetic resonance studies on VO(II) doped cadmium ammonium phosphate hexahydrate were carried out at room temperature. The paramagnetic impurity VO(II) was found to enter the host lattice both substitutionally and interstitially. The spin Hamiltonian parameter values calculated from crystal rotations for both the locations are; Site1: g∥ = 1.939, g⟂ = 1.992, A∥ = 16.3mT, A⟂ = 7.7mT and site2: g∥ = 1.933, g⟂ = 1.998, A∥ = 16.2mT, A⟂ = 7.7mT. The powder spectra values agree well with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a large number of EPR studies on vanadyl ion in various host lattices [2][3][4][5][6][7][8][9][10][11], experiments have shown that the V(IV) ion of VO(II) is surrounded by a distorted octahedron in which the vanadyl bond VQO has a well-defined orientation [12], since the EPR spectrum is very sensitive to the crystalline environment. The behaviour of unpaired electron in VO(II) complexes is dominated by the strong VQO bond.…”
Section: Introductionmentioning
confidence: 99%
“…In a large number of EPR studies on vanadyl ion in various host lattices [2][3][4][5][6][7][8][9][10][11], experiments have shown that the V(IV) ion of VO(II) is surrounded by a distorted octahedron in which the vanadyl bond VQO has a well-defined orientation [12], since the EPR spectrum is very sensitive to the crystalline environment. The behaviour of unpaired electron in VO(II) complexes is dominated by the strong VQO bond.…”
Section: Introductionmentioning
confidence: 99%